Service Quality as a Determinant of Customer Satisfaction in Islamic Education - Asrian Noor; Siti Julaiha (Journal of Educational Management Research, 2025)
Quality management and service quality are strategic components in improving customer satisfaction in Islamic educational institutions. This study aims to analyze the contribution of service quality to internal and external customer satisfaction using the SERVQUAL theory in the context of Islamic education. The method used is a literature review of the literature on education quality management, service quality, and customer satisfaction. The results of the study show that five dimensions of service quality, namely physical evidence, reliability, responsiveness, assurance, and empathy, have a significant influence on the level of customer satisfaction. Internal customer satisfaction, especially teachers and education staff, also plays an essential role in supporting sustainable service quality. The implications of this research emphasize the need to develop an integrated quality system, enhance human resource competence, and strengthen communication between educational institutions and customers to deliver superior, responsive Islamic education services that meet the needs of stakeholders.